Case Report: Sneaky DCIS-like invasive ductal carcinoma of the breast in the setting of extensive DCIS - Chen, Chong; Tie, Yateng; Zhang, Xinjuan; Hou, Niuniu; Song, Yun; Ren, Dong (Frontiers in Medicine, 2025)
In most cases, invasive ductal carcinoma (IDC) of the breast is identifiable when it presents with classic infiltrative growth patterns. However, a subset of IDC can present in a very sneaky way, significantly mimicking the appearance of ductal carcinoma in situ (DCIS). In this condition, it is much easier to miss the invasive component without pulling ancillary staining when morphologic findings are extremely compatible with DCIS, especially the diagnosis of DCIS was made on the previous biopsy. Here, we report the case of a 55-year-old female patient who was found to have microcalcifications at the 11:00 o’clock position in the right posterior breast during a routine mammographic examination. A biopsy of the calcification area performed at an outside hospital reported high-grade DCIS (ER+, PR−). Histologic examination of the subsequent mastectomy specimen at our institution showed two separate areas that closely resembled DCIS. Immunohistochemical (IHC) staining showed that all myoepithelial markers—smooth muscle myosin heavy chain (SMMHC), p63, CK5/6, and S100—were retained at the periphery of the expanded acini in one of the areas. Unexpectedly and surprisingly, myoepithelial markers were completely lost at the periphery of a subset of the DCIS-looking acini in another area, a finding that was immunohistochemically consistent with the diagnosis of invasive ductal carcinoma admixed with DCIS. Knowing that invasive ductal carcinoma of the breast can exhibit a DCIS-like morphology, especially in cases where a prior biopsy has already established a diagnosis of DCIS, will enhance the awareness of pathologists to recognize invasive ductal carcinoma that mimics DCIS. In turn, this will prevent misdiagnosis and undertreatment of patients with invasive ductal carcinoma of the breast.